2020
DOI: 10.3390/jcm9030839
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Patients with Acute Myocardial Infarction Supported with Extracorporeal Membrane Oxygenation

Abstract: Background: There are limited data on complications in acute myocardial infarction (AMI) admissions receiving extracorporeal membrane oxygenation (ECMO). Methods: Adult (>18 years) admissions with AMI receiving ECMO support were identified from the National Inpatient Sample database between 2000 and 2016. Complications were classified as vascular, lower limb amputation, hematologic, and neurologic. Outcomes of interest included temporal trends, in-hospital mortality, hospitalization costs, and length of stay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
(49 reference statements)
1
29
0
2
Order By: Relevance
“…ECMO support was identified (ICD-9CM 39.65; ICD-10CM 5A15223) consistent with prior literature [6,9,10]. Deyo's modification of the Charlson Comorbidity Index was used to identify comorbid diseases, and prior methodology was used to identify cardiac and non-cardiac procedures (Table S1) [1,2,6,9,15]. Similar to prior work from the HCUP-NIS, the timing of IHCA and ECMO were calculated using the day of the procedure, and simultaneous ECMO insertion was defined as that performed on the same hospital day as the IHCA [1,2,9,10,17,18].…”
Section: Methodssupporting
confidence: 81%
See 3 more Smart Citations
“…ECMO support was identified (ICD-9CM 39.65; ICD-10CM 5A15223) consistent with prior literature [6,9,10]. Deyo's modification of the Charlson Comorbidity Index was used to identify comorbid diseases, and prior methodology was used to identify cardiac and non-cardiac procedures (Table S1) [1,2,6,9,15]. Similar to prior work from the HCUP-NIS, the timing of IHCA and ECMO were calculated using the day of the procedure, and simultaneous ECMO insertion was defined as that performed on the same hospital day as the IHCA [1,2,9,10,17,18].…”
Section: Methodssupporting
confidence: 81%
“…Prior studies have shown administrative codes to have a high sensitivity and specificity for identification of IHCA [1,2,15,16]. ECMO support was identified (ICD-9CM 39.65; ICD-10CM 5A15223) consistent with prior literature [6,9,10]. Deyo's modification of the Charlson Comorbidity Index was used to identify comorbid diseases, and prior methodology was used to identify cardiac and non-cardiac procedures (Table S1) [1,2,6,9,15].…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…However, since the HCUP-NIS database does not track patients across hospital admissions, this hypothesis will need additional studies for confirmation. We have previously shown that complications are associated with higher in-hospital resource utilization and therefore judicious patient selection is key to employ these devices [36].…”
Section: Plos Onementioning
confidence: 99%